The Role of Need for Affect and Need for Cognition in Self-Evaluation - Aquino, Antonio; Haddock, Geoffrey; Maio, Gregory R.; Alparone, Francesca Romana (Psychology Hub, 2020)
The primary aim of this study was to investigate whether individual differences in affective and cognitive orientation predict the relative importance of warmth-related and competence-related traits in self-evaluation. 99 participants (85 females) completed the Need for Affect and Need for Cognition scales. Later, participants rated the extent to which warmth- and competence-related traits described their own personality. In line with our hypotheses, affective people expressed more positive evaluations of warmth traits and more negative evaluations of cold traits relative to cognitive people, who expressed more positive evaluations of competence traits and more negative evaluations of incompetence traits. This differentiation has implications for self-evaluation processes and individual differences in affective and cognitive orientation.